2022
DOI: 10.1155/2022/9155080
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Values of Serum IL-33 and sST2 in Endotypes and Postoperative Recurrence of Chronic Rhinosinusitis with Nasal Polyps

Abstract: Background. Chronic rhinosinusitis with nasal polyps (CRSwNP) is a common inflammatory disease with high heterogeneity and postoperative recidivation. The IL-33/ST2 axis is known to be involved in Th2 immune responses. This study is aimed at exploring levels of serum IL-33 and soluble ST2 (sST2) in CRSwNP patients and their potential for predicting CRSwNP endotypes and postoperative recurrence. Methods. The present study recruited 149 CRSwNP patients, 80 of whom were noneosinophilic (neCRSwNP) and 69 eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition, a larger spike of human DNA would be a useful progression of this model. A proportion of ~ 99% human DNA typically seen in swab samples would better simulate the challenges faced in sequencing sinus microbiome samples [41][42][43] . This mock community would also be more suitable for the task of ne-tuning DNA extraction methods, including the potential use of host DNA depletion steps and aspects of computational genomics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a larger spike of human DNA would be a useful progression of this model. A proportion of ~ 99% human DNA typically seen in swab samples would better simulate the challenges faced in sequencing sinus microbiome samples [41][42][43] . This mock community would also be more suitable for the task of ne-tuning DNA extraction methods, including the potential use of host DNA depletion steps and aspects of computational genomics.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, most of the research evaluates serum IL-33 levels versus tissue IL-33, so part of the difference in terms of the consistency of the results with the literature can be attributed to this fact. For example, Zhang et al [34] suggested that serum IL-33 levels were upregulated in CRSwNP patients and related to the degree of mucosal eosinophil infiltration and postoperative recurrence. Thus, IL-33 might serve as an objective biomarker for predicting recurrence in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, we applied the scale developed by Georgalas et al, due to the complexity of its structure, its simplicity of evaluation, and its direct correlation with the Lund-Mackay score. The osteitis was thus classified as not significant (<5), mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), or severe (higher than 35), as presented in Table 3 [5,18].…”
Section: Computed Tomography (Ct) Scan In Clinical Practice In Crswnpmentioning
confidence: 99%